Cost Analysis of Reclaimed Asphalt Concrete for Rigid Pavement Construction. - Ariho, Dan (Kabale University, 2023)
This study evaluated the feasibility and cost effectiveness of using reclaimed asphalt (RAP) as aggregates in production of concrete for rigid pavements. The RAP material was obtained from Kabaraga in Kabale along Kabale-Mbarara highway crushed to obtain the desired sizes and subjected to laboratory tests i.e. particle size distribution, bulk density and relative density for both coarse and fine aggregates. Concrete samples of nominal mixes1:3:6 and 1:2:4 at varying water cement ratios of 0.4, 0.5 and 0.6 were prepared and tested for slump. 15 concrete cubes of 150mm x 150 mm x 150 mm per concrete mix per w/c ratio were cast and subjected to curing under water after 24 hours of casting. The cubes were then tested for compressive strength after 3, 7, 14, 28 and 56 days of curing and a minimum of 3 cubes were crushed and results recorded. The results analysis for compressive strength indicates that there was a progressive increase in compressive strength at different curing days for both RAP and normal concrete, having the highest values at 56 days of 10.800, 15.900 and 13.170 Mpa for a 1:2:4 mix of conventional concrete at 0.4, 0.5 and 0.6 water cement ratios and 4.923, 8.290 and 8.067 Mpa for 1:3:6 mixes of 0.4, 0.5 and 0.6 respectively. While for RAP concrete compressive strength at 56 days were, 5.367, 6.003 and 9.533Mpa for 1:2:4 and 3.767, 4.750 and 5.367 Mpa for 1:3:6 mix at 0.4, 0.5 and 0.6 water cement ratios respectively. A unit cost analysis for producing a m3 of RAP concrete and normal concrete showed that, utilization of RAP as aggregates in production of 1m3 of concrete will yield a cost saving of about 20% and 14% resulting from the use of RAP in production of concrete for mixes 1:3:6 and 1:2:4 respectively. It was therefore concluded that, concrete produced with RAP aggregates at 1:2:4 w/c ratio of 0.5 can be used for rigid pavement construction of low traffic and pedestrian walk-ways based on strength and cost criterion.